Penguatan Nilai Hidup Orang Basudara melalui Bimbingan Kelompok untuk Meningkatkan Kohesivitas di SMA PGRI Oma- Haruku - Theophanny P. Th Rampisela; Febrinex Christine Mairuhu; Prisca Diantra Sampe (Elevasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2026)
Living in brotherhood is the Maluku philosophy of life. This philosophy is a legacy that is deeply ingrained in family life. Over time, this philosophy has become less widely used and often becomes unimportant. Therefore, this philosophy will be used to help improve student cohesion. The method used is group guidance techniques, which guide students in improving cohesion. The program results show that strengthening the value of living in brotherhood through group guidance effectively increases high school student cohesion. This process successfully changes students' social interaction patterns from individualistic to collective, from exclusive to inclusive, and from less caring to more empathetic and cooperative.